Framing of research question using the PICOT format in randomised controlled trials of venous ulcer disease: a protocol for a systematic survey of the literature - Abbade, Luciana P F; Wang, Mei; Sriganesh, Kamath; Mbuagbaw, Lawrence; Thabane, Lehana (BMJ, 2016)
INTRODUCTION: Although venous ulcers have a great social and economic impact, there is a lack of evidence from randomised controlled trials (RCTs) to support appropriate management for this disease. Framing the research question using the Population; Intervention; Comparator; Outcome; Time frame (PICOT) format in RCTs can improve the quality of the research design. OBJECTIVES: To evaluate how the PICOT format is used to frame a research question in reports of RCTs of venous ulcer disease and to determine the factors associated with better adherence to the PICOT format in framing the research question. METHODS AND ANALYSES: We will conduct a systematic survey of RCTs on venous ulcers published in the National Institute of Health, PubMed database between January 2009 and May 2016. We will include all RCTs addressing therapeutic intervention for venous ulcer disease involving human subjects, and published in the English language. The selection process will be carried out in duplicate by two independent investigators. First, titles and abstracts will be screened, then full-text articles. We will examine whether the five elements of the PICOT format are used in formulating the research question and give a score between 0 and 5. The primary outcome will be the proportion of studies that have adequately reported all five PICOT elements. DISSEMINATION: This will be the first survey to assess how the PICOT format is used to frame research questions on the management of venous ulcers in reports of RCTs. On completion, this review will be submitted to a peer-reviewed biomedical journal for publication and the findings will also be presented at scientific conferences.
Keywords: Randomized controlled trial; STATISTICS & RESEARCH METHODS; Venous ulcers; WOUND MANAGEMENT